Pengaruh Motivasi Kerja, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Koperasi Perindustrian dan Perdagangan Kabupaten Kerinci - Dona Elvia Desi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2020)
This study aims to determine the effect of work motivation, work environment and work discipline on the performance of employees of the Office of Cooperative Industry and Trade (Diskoperindag) Kerinci Regency in 2019. The method used is descriptive quantitative and primary data obtained from a sample of 49 civil servants, analysis tools in the form of multiple linear regression and determinant coefficient, as well as hypothesis testing using the t-test and F test. The results show that part there is a positive and significant influence between work motivation, work environment and work discipline on the performance of the Diskoperindag staff in Kerinci Regency with the magnitude of the influence of each of which is 27.87%, 3.86% and 24.76%. It is recommended to pay attention to other factors to maintain and improve the performance of the employees of Diskoperindag Kerinci Regency.